Molecular Identification of Candida species isolated from patients with vulvovaginitis for the first time in Mashhad - Zahra Kord; Abdolmajid Fata; Hossein Zarrinfar (Mashhad University of Medical Sciences, 2017)
Introduction: Vulvovaginal candidiasis (VVC) is one of the most common vaginal infection in women of childbearing age. In some cases, due to the intervention of resistant strains of Candida albicans and non-albicans species, recurrent vulvovaginal candidiasis (RVVC) occurs. This study was performed with aim to identify the Candida isolated from patients with vulvovaginal candidiasis by PCR-RFLP method. Methods: This descriptive study was performed on 189 vaginal discharge obtained from women with clinical presentation of VVC referred to Ghaem Hospital, Mashhad University of Medical Sciences during 2015-2016. The vaginal discharge was examined by direct examination and culture on Sabouraud's dextrose agar medium for definitive diagnosis. The genomic DNA of Candida colonies have grown in culture were extracted by boiling lysis method. The Candida isolates were identified by PCR-RFLP technique. The results were analyzed by SPSS software (version 16) and using Pearson and Chi-square test. PResults: Among 189 sampled patients, 108 positive Candida cultures were acceptable. The Candida species which were identified included C. albicans 84 (77.8%), C. glabrata 10 (9.3%), C. kefyr 4 (3.7%), C. parapsilosis 1 (0.9%) and C. tropicalis 1 (0.9%). About 8 (7.4%) of the specimens contained two species of Candida. RVVC form was observed in 5 (4.6%) of the patients. Conclusion: The most common cause of VVC was C. albicans; and C. glabrata had the highest frequency among the non-albicans species. Most of patients had non- RVVC.